A Comprehensive Multidisciplinary Strategy for the Management Of Musculoskeletal Fractures Throughout Pregnancy: Evaluation, Treatment, And Maternal-Fetal Considerations - Madkhali, Nabeel Ahmed Mohammed; alsomali, Mona dullah yousef; Al-Dosari, Yousra Nasser Mohammed; ALHarbi, Sultan Tulayhan Ayed; F. ALRUWAILI, SALAMAH TIRAD; Alahdal, Ahood Abdurahman Mohammed; almutiri, Gazwa hindi dara; Alwayel, Hussain Abdultef; Alsaif, Alaa hussain; Alamoudi, Daad Saeed; Aljuaid, Eman Sulaiman A; Somaili, Essa Ali (Journal of Ecohumanism, 2024)
Because of physiological, anatomical, and pharmacological changes that impact diagnostic and treatment strategies, pregnancy-related fractures pose special difficulties. Prioritizing the safety of the mother and fetus necessitates interdisciplinary teamwork.The purpose of this review is to investigate current understanding and recommended practices for multidisciplinary fracture therapy during pregnancy, with a focus on diagnostic safety, treatment options, and maternal-fetal outcomes.Case reports, clinical recommendations, and pertinent reviews were included in a narrative evaluation of the body of available literature. In the context of pregnancy, the analysis addressed surgical decision-making, postpartum care, anesthetic concerns, and diagnostic imaging modalities.Pregnancy-related physiological alterations that impact trauma treatment include increased blood volume, ligamentous laxity, and altered medication metabolism. Diagnostic imaging techniques like MRI and ultrasound are thought to be safe, although they may provide dangers to the fetus. When surgery is required, gestational age must be taken into account; for non-emergency surgeries, the second trimester is favored. For the best results, a multidisciplinary team that includes neonatologists, obstetricians, orthopedic surgeons, and anesthesiologists is essential. When possible, regional anesthesia is preferred over general anesthesia. Fetal monitoring and thromboprophylaxis are part of postoperative care.A coordinated, multidisciplinary strategy is necessary to efficiently manage fractures in pregnant women while striking a balance between the requirements of the mother and the safety of the fetus. In order to minimize difficulties and guarantee positive results for both mother and child, early preparation, risk assessment, and customized treatment are essential.